Classroom Management in DC Public School: Coolidge Senior High School - Muhammad Ari Saputra (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
Teaching a language is a scientific process to give knowledge of language to the students in order that the students enable to communicate through in written and spoken form with one another. The students are able to communicate in spoken and written English accurately, fluently and in good manners. Managing a class full of students is one of the biggest challenges faced by teachers. If teachers do not have an effective plan in place, there will not be much opportunity for students to engage in meaningful learning experiences. Thus, teachers will find themselves refereeing instead of teaching. Classroom management is a term used by teachers to describe the process of ensuring that classroom lessons run smoothly despite disruptive behavior by students. Classroom management means teachers’ strategies to create and maintain an orderly learning environment and discipline means teachers’ responses to students’ misbehavior. The goal of classroom management is to create and maintain a positive, productive learning environment, to support and foster a safe classroom community, to assist students to keep task focused, to reduce distraction from learning, to organize and facilitate the flow of learning activities and to help the students to manage them. This is part want to analysis the video taken from YouTube; focus on native or first language in English language teaching on senior high school level. The video coming to DC Public School: Coolidge Senior High School.